Microorganisms-promoted biodiesel production from biomass: A review - Huan Wang; Xiaodong Peng; Heng Zhang; Song Yang; Hu Li (Energy Conversion and Management: X, 2021)
Biodiesel is considered as a potential substitute for fossil fuel due to its renewability, sustainability, environmentally friendliness, and biodegradability, especially with comparable fuel properties to diesel. The chemocatalytic production of biodiesel from plant oils is widely used in industrial production due to its low cost and high conversion rate. However, the disadvantages are high energy consumption and environmentally unfriendly processing such as chemical catalysts, downstream technology and simultaneously produced waste. Therefore, in the past decade, enzyme-catalyzed biodiesel has attracted more attentions due to its sustainability and environmental friendliness. High-cost, enzyme stability and reusability are the main obstacles to the large-scale industrial development of microbial biodiesel. This review first showcases the state-of-the-art of microbial biodiesel production, including (1) lipid accumulation of oleaginous microorganisms from pretreated lignocellulose biomass, and (2) production of biodiesel from microbial oils via transesterification by immobilized lipase. Also, the technological challenges and future developmental trends are discussed, with the goal of providing the possibility of more economical large-scale industrial production. This paper provides opportunities for the sustainable and eco-friendly production of enzymatic biodiesel in the future.